Size-tailored synthesis of gold nanoparticles and their facile deposition on AAO-templated carbon nanotubes via electrostatic self-assembly: Application to H2O2 detection. (November 2015) - Pannopard, Panvika; Boonyuen, Chaiyan; Warakulwit, Chompunuch; Hoshikawa, Yasuto; Kyotani, Takashi; Limtrakul, Jumras
Abstract: The use of gold nanoparticle/carbon nanotube composite (AuNP/CNT) is of current interest in the development of nanomaterial based sensing and electronic devices. Herein, we demonstrate a novel method to tailor the size of positively charged AuNPs under the influence of two capping agents, polyvinylpyrrolidone (PVP) and 4-dimethylaminopyridine (DMAP). By varying the mole ratios of PVP:DMAP (P:D) from 1:32 to 32:1, the average diameters of AuNPs were progressively decreased from 17.3 nm to 1.8 nm. Therefore, PVP played a dominant role in the formation of small AuNPs. Moreover, these size-controlled AuNPs could be electrostatically deposited onto the anodic aluminum oxide (AAO)-templated CNTs without requiring a pretreatment of the CNT surfaces. The obtained AuNPs/CNTs with different Au core sizes were also compared in terms of electroactivity towards hydrogen peroxide (H2 O2 ) reduction. The greatest voltammetric response was of Au-(P1:D4-10.6 nm)/CNTs caused by their reduced charge transfer resistance from the low covering of PVP on the Au surfaces and by their dense and uniform AuNPs. This modified electrode also provided a wide linearity range for H2 O2 detection from 5 μM to 45.80 mM with the low detection limit of 0.23 μM (S/N = 3). This study thus suggests the rational design of AuNP/CNT structure for an H2 O2 sensor.